Pull-forward effects in the German car scrappage scheme: A time series approach - Veit Böckers; Ulrich Heimeshoff; Andrea Müller (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
The focus of this paper is the empirical evaluation of the German Accelerated Vehicle Retirement program, that was implemented in January 2009 to stimulate automobile consumption. To adress this question a monthly dataset of new car registrations owned by private consumers from March 2001 until October 2011 is created. Especially small and upper small car segments seem to have profited from the scrappage program as they make up 84% of the newly registered cars during the program. Using uni- and multivariate time-series models counterfactual car registrations are estimated for vehicles from the small and upper small car segment. The results suggest that the policy has been successful in creating additional demand for new cars during the policy period. We also find a small contraction in the year after the end of the policy for the small market segment. For upper small cars the pull-forward effect could only be identified for the last quarter of the ex-post period. So in summary, the overall effect of the German car scrappage program is positive for the two market segments.
Keywords: 330; Kraftfahrzeug; Schrott; Subvention; Wirkungsanalyse; Personenkraftwagen; Nachfrage; Marktsegmentierung; Deutschland